Doggo and Pupper - Book 1 - Applegate, Katherine; Adler, Charlie (New York : Feiwel & Friends, 2021)
Doggo, an older dog, learns how to welcome and accept a young puppy into the household.
Keywords: Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Dogs -- Fiction; Friendship -- Fiction